Aortic Deceleration Injury Treated by Endograft: A Case Report with 11-Year Followup. (24th December 2012) - Hu, Zhi-Wei; Gao, Wang-Zhong; Gu, Yong-Quan; Chen, Bing; Zhu, Guang-Chang; Liang, Wei-Tao; Ning, Ya-Chan
Abstract : Aortic deceleration injury is a common and critical condition following automobile accident with high fatality. The survivors complicated with associated serious injuries are even rare and definitive treatment is required. A 37-year-old male patient had both aortic blunt injury and coronary artery injury after a frontal car collision. After failed coronary artery percutaneous transluminal angioplasty (PTA) and deteriorated aortic lesion, the ruptured aorta was subsequently successfully treated by us with a self-made individualized endograft. The endograft was well in position and the patient functioned well in 11-year followup. With the development of endograft and technique, the endovascular treatment may be an option for patients with complicated aortic blunt injury. Yet careful patient selection and the long-term followup are essential.